Trigonometrically-fitted higher order two derivative Runge-Kutta method for solving orbital and related periodical IVPs - Ahmad, Nur Amirah; Ismail, Fudziah; Senu, Norazak (Hacettepe University, 2019)
In this paper, a trigonometrically-fitted two derivative Runge-Kutta method (TFTDRK)of high algebraic order for the numerical integration of first order Initial Value Problems(IVPs) which possesses oscillatory solutions is constructed. Using the trigonometrically-fitted property, a sixth order four stage Two Derivative Runge-Kutta (TDRK) methodis designed. The numerical experiments are carried out with the comparison with otherexisting Runge-Kutta methods (RK) to show the accuracy and efficiency of the derivedmethods.